Analisis Kelengkapan Rekam Medis Rawat Inap Rumah Sakit Ganesha Di Kota Gianyar Tahun 2019 - Ni Luh Putu Devhy; Anak Agung Gede Oka Widana (Jurnal Rekam Medis dan Informasi Kesehatan, 2019)
Hospital is an organization engaged in services, therefore it is obliged to hold a medical record for the achievement of good administration. Registration, data filling, processing and analysis as well as documentation, this is the process of organizing medical records. Filling in the medical record is said to be good if each item on the medical record sheet is filled with complete data. A complete medical record is a quality image of a hospital.Based on the above background, the researcher wants to find out the percentage of completeness of medical record filling in the inpatients of Ganesa hospital in the city of Gianyar. This type of research is a descriptive study with a cross-sectional design. The sample in this study was 95 inpatient medical record files. Percentage of completeness for RM Patient identity is 100%, doctor's identity is 96.8%, nurse's identity is 85.3%, informed consent is 95.8%, anesthesia is 43.2%, resume is 100%, diagnosis is 100%, abbreviations of 66.3%, readability of 76.8%, rectification of 23.2% and structuring of 100%. The incompleteness in filling the inpatient medical record at the Ganesha Gianyar Hospital was highest in the correction item.